Environmental Justice and mining. Past and present spatialities - Bastos, Bárbara (Antropologia Pubblica, 2024)
Environmental justice aims to simultaneously face environmental collapse and social disparities, fostering the reproduction of material conditions that underlies the habitability of life on Earth. Extractive operations are one of the main features of capitalism and there is no foreseeable future without mineral extraction. Intensive mining contributes to environmental harms meanwhile prevails over trust on technocratic solutions to ecological degradation. Considering mining closure processes and ongoing raw material extraction, this report aims to present a preliminary analysis of empirical data gathered during a doctoral research conducted in both Iglesias (Sardinia) and Vazante (Minas Gerais, Brazil) on the ontological dimensions of environmental justice in extractive contexts. This report is particularly focused on drawing out ways from which extraction underpins communities' relations in and with territories in different historical periods and geopolitical contexts.